WHSC1 links transcription elongation to HIRA‐mediated histone H3.3 deposition. (6th August 2013) - Sarai, Naoyuki; Nimura, Keisuke; Tamura, Tomohiko; Kanno, Tomohiko; Patel, Mira C; Heightman, Tom D; Ura, Kiyoe; Ozato, Keiko
<x xml:space="preserve">Abstract</x> Actively transcribed genes are enriched with the histone variant H3.3. Although H3.3 deposition has been linked to transcription, mechanisms controlling this process remain elusive. We investigated the role of the histone methyltransferase Wolf–Hirschhorn syndrome candidate 1 (WHSC1) (NSD2/MMSET) in H3.3 deposition into interferon (IFN) response genes. IFN treatment triggered robust H3.3 incorporation into activated genes, which continued even after cessation of transcription. Likewise, UV radiation caused H3.3 deposition in UV‐activated genes. However, in Whsc1−/− cells IFN‐ or UV‐triggered H3.3 deposition was absent, along with a marked reduction in IFN‐ or UV‐induced transcription. We found that WHSC1 interacted with the bromodomain protein 4 (BRD4) and the positive transcription elongation factor b (P‐TEFb) and facilitated transcriptional elongation. WHSC1 also associated with HIRA, the H3.3‐specific histone chaperone, independent of BRD4 and P‐TEFb. WHSC1 and HIRA co‐occupied IFN‐stimulated genes and supported prolonged H3.3 incorporation, leaving a lasting transcriptional mark. Our results reveal a previously unrecognized role of WHSC1, which links transcriptional elongation and H3.3 deposition into activated genes through two molecularly distinct pathways.